2020
DOI: 10.2147/rmhp.s272527
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association Between Caustic Ingestion and Psychiatric Comorbidity Based on 396 Adults Within 20 Years</p>

Abstract: High prevalence of psychiatric comorbidities (PCs) has been widely documented in caustic substance ingestion cases. However, their effect on the clinical features and prognostic outcomes remains unclear due to the paucity of discussion. We report on detailed clinical courses with long-term multifaceted outcomes and review the association between caustic ingestion and each specific PC. Patients and Methods: The retrospective chart review included 396 adults (median follow-up, 16.6 months) with and 377 without (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…A national population-based study has indicated that patients with psychiatric disorders are more likely to have GI corrosive injury than persons without mental illness [ 6 ]. In addition, previous studies have reported that patients with psychiatric disorders have a worse prognosis after accidentally ingesting corrosive substances compared with people without mental illness, which may be related to the higher intake amount [ 7 ]. However, some articles had a different point of view and suggested that patients with a history of psychopathology might have a better outcome of corrosive esophageal injury because caregivers are more likely to be on the lookout for warning signs in these patients, and act promptly by bringing them to medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…A national population-based study has indicated that patients with psychiatric disorders are more likely to have GI corrosive injury than persons without mental illness [ 6 ]. In addition, previous studies have reported that patients with psychiatric disorders have a worse prognosis after accidentally ingesting corrosive substances compared with people without mental illness, which may be related to the higher intake amount [ 7 ]. However, some articles had a different point of view and suggested that patients with a history of psychopathology might have a better outcome of corrosive esophageal injury because caregivers are more likely to be on the lookout for warning signs in these patients, and act promptly by bringing them to medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study based on 396 adults, Chen et al [14] in Taiwan reported that the presence of psychiatric comorbidities predicted severe endoscopic lesions of the upper GI tract, higher rates of surgical admission and intensive care unit stay, an increase in systemic and gastrointestinal complications and poorer 5-year relative survival rates in patients with caustic ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…The event of corrosive ingestion itself is highly stressful and often performed as a suicidal act in adults [ 8 ]. During the chronic phase, individuals with refractory strictures suffer from dysphagia, aspiration, malnutrition, social isolation, multiple hospital visits, and a poor quality of life [ 3 , 16 , 17 ]. Thus, there is a need to gather patient-reported outcomes to help clinicians decide whether repeated endoscopic dilation of corrosive-induced esophageal strictures is appropriate and beneficial to patients.…”
Section: Introductionmentioning
confidence: 99%